iDisorder : understanding our obsession with technology and overcoming its hold on us. - Carrier, L. Mark, ....-; Cheever, Nancy A., ....-; Rosen, Larry D., ....- (New York : Palgrave Macmillan, 2012)
IDisorder: changes to your brain's ability to process information and your ability to relate to the world due to your daily use of media and technology resulting in signs and symptoms of psychological disorders - such as stress, sleeplessness, and a compulsive need to check in with all of your technology. Based on decades of research and expertise in the 'psychology of technology,' Dr. Larry Rosen offers clear, down-to-earth explanations for why many of us are suffering from an 'iDisorder.' Rosen offers solid, proven strategies to help us overcome the iDisorder we all feel in our lives while still making use of all that technology offers. Our world is not going to change, and technology will continue to penetrate society even deeper leaving us little chance to react to the seemingly daily additions to our lives. Rosen teaches us how to stay human in an increasingly technological world.
Keywords: Multimedia